Effectiveness of integrating Eduwebtv resources on form two students' achievement in learning science - Mahmud, Rosnaini; Ismail, Mohd Arif; Ahmad, Siti Salbiah; Abdul Rahman, Fadzilah; Kamarudin, Nurzatulshima (Elsevier, 2012)
This study evaluated the effects of integrating resources from the Eduwebtv online portal on students’ achievement in learning science. The study employed quasi experimental design using pre and post tests. Two classes of Form Two secondary school students were randomly assigned to the experimental (n=32) and control (n=30) intact groups. The experiment involved ten science class sessions. Students in both groups received similar content on the topic ‘Dynamic, Support and Movement’ and taught by the same teacher. For the treatment group the teacher integrated video-based resources obtained from the Eduwebtv portal to teach the topic. On the other hand, the control group was taught in the conventional way, without the video-based resources. Achievement in learning the topic was assessed using two similar sets of validated teacher-designed tests administered before and after the experiment. Data were analyzed by Statistical Packages for the Social Sciences (SPSS) version 15.0. using descriptive (mean, frequency, percentage & standard deviation) and inferential statistics (t-test). Findings demonstrated that there was a significant difference in students’ achievement in the post-test in the treatment group (M = 51.75, SD = 7.45) compared to the control group (M = 41.87, SD = 6.85); t(29) = 5.361, p<0.05.